THE ULTIMATE EGO AS CO-CREATOR: IQBAL’S DYNAMIC THEISM AND THE RE-ENCHANTMENT OF HUMAN AGENCY IN A POST-MECHANISTIC COSMOS - Faheem Ul Haq (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
Muhammad Iqbal (1877–1938), a pivotal figure in modern Islamic thought, poet, and philosopher, articulated a profound metaphysical system that reimagines God as the Ultimate Ego—a dynamic, creative, and personal entity engaged in perpetual creation. This framework elevates humanity to the status of co-creators through the cultivation of khudi (selfhood or ego), a concept that emphasizes individuality, freedom, and purposeful action. Rejecting both the static determinism of mechanistic science and the passive annihilation of traditional Sufi mysticism, Iqbal’s dynamic theism integrates Qur’anic teachings, Sufi insights (selectively critiqued), and influences from Western philosophers like Henri Bergson and Friedrich Nietzsche to foster a re-enchanted worldview. In a post-mechanistic cosmos informed by quantum mechanics and relativity, where reality is probabilistic and relational rather than rigidly deterministic, Iqbal’s philosophy restores human agency, meaning, and wonder. This paper delves into the intricacies of Iqbal’s ideas, exploring their historical context, key components, philosophical implications, critiques, and contemporary relevance, arguing that they provide a robust foundation for empowering individuals in an era of scientific and existential uncertainty.